Joias inspiradas no patrimônio arquitetônico da Vila Belga, Santa Maria/RS - Genro, Luize Brum (2023)
The master's thesis is part of the Architecture and Material Heritage concentration area Architecture and Material Heritage and the Preservation and Material Heritage research line of the postgraduate program at the Federal University of Santa Maria/RS. The present work aims to develop a collection of jewelry as souvenirs inspired by the built heritage of Vila Belga, using techniques and materials from artisanal goldsmithing. Starting from the proposal to use the built heritage present in Vila Belga in Santa Maria, RS, as inspiration, a brief history of the emergence of Vila Belga is discussed, as well as the understanding of built cultural heritage, the history of the jewel and the jewel such as material culture, knowledge about souvenirs and an approach to jewelry inspired by built heritage. As a source of inspiration, elements present in the architecture of the houses present in Vila Belga were used. The design methodology of Löbach (2001) was chosen for the development of the project. With this, this project seeks to contribute to the enhancement of the territory's identity, where the historical and symbolic heritage present in the architecture of the houses in Vila Belga will serve to enhance and preserve its material value present in the elements of local architecture in the universe of contemporary jewelry, enabling the user the historical and cultural knowledge present in the place.